-3x+3y=3
-5x+y=13
Solve for substitution
1 answer:
Take -5x + y =13 and rearrange for y:
y=13+5x
Substitute into other equation for y:
-3x+3(13+5x)=3
Multiply out brackets:
-3x+39+15x=3
Simplify:
12x+39=3
Rearrange for x:
12x=-36
x=-3
Substitute back into y=13+5x:
y=13+5(-3)
y=13-15
y=-2
You might be interested in
C(x) = 5x + 2
This is because at 1 hour it only cost 7 dollars, so it should only have 2 added to the end.
Answer:
1. k = 15
2. d = 20
3. n = 3
Answer:
g
Step-by-step explanation:
B, because percent means per 100.
Answer:
-220
Step-by-step explanation: